Bibliometric Analysis: Green Human Resources Impact on Performance Management - Yudho Novandhika Putra; Muhammad Andriyan Fikri; Laylatul Inaya (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2023)
Abstract Purpose – This study aims to evaluate to scholarly performance of articles on Green Human Resource Management (GHRM) and analyze their impact, while also providing a scientific mapping of the literature concerning GHRM and its influence on organizational performance. Methodology – This study employed bibliometric analysis to map the intellectual landscape of GHRM and to assess the performance and impact of related scholarly publications. The bibliometric techniques applied include performance analysis and science mapping. Data for the analysis were sourced from the Scopus database. Findings – The analysis indicates a growing trend in GHRM related research publications between 2012 and 2023. The bibliometric findings indicate that GHRM positively contributes to sustainable and environmental performance, supports green supply chain management practices, and fosters pro-environmental employee behavior. Additionally, several studies underscore the positive impact of GHRM on both employee environmental attitude and overall organizational performance. Research Limitation – This study is limited by the scope of data available within the Scopus database. Furthermore, the analysis is constrained by its focus on selected scientific publications, potentially excluding other relevant sources of information. Practical Implications – HR professionals and policymakers should integrate these practices strategically and encourage collaboration across departments to meet stakeholder expectations and sustain competitiveness.